2017
DOI: 10.1099/jmm.0.000574
|View full text |Cite
|
Sign up to set email alerts
|

The spa typing of methicillin-resistant Staphylococcus aureus isolates by High Resolution Melting (HRM) analysis

Abstract: Molecular typing is an important tool for control and prevention of infection. A suitable molecular typing method for epidemiological investigation must be easy to perform, highly reproducible, inexpensive, rapid and easy to interpret. In this study, two molecular typing methods including the conventional PCR-sequencing method and high resolution melting (HRM) analysis were used for staphylococcal protein A (spa) typing of 30 Methicillin-resistant Staphylococcus aureus (MRSA) isolates recovered from clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 11 publications
3
20
1
Order By: Relevance
“…This finding is in line with the findings of Hon-Kwan Chen et al study in China [8]. However, our results were in contrast with the results of Fasihi et al [11] and…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is in line with the findings of Hon-Kwan Chen et al study in China [8]. However, our results were in contrast with the results of Fasihi et al [11] and…”
Section: Resultssupporting
confidence: 89%
“…The MRSA isolates were obtained from patient's skin (19, 38%), Blood (10,20%), wound (8,16%), Sputum diagnostics. HRM method can easily and rapidly identify the different alleles of spa genes [11]. This method is used in a closed system and in the same tube as the amplification step; hence, it is faster, easier, and more suitable for high sample, which reduces the risk of contamination [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, typing and analysis of MRSA strains have become a routine procedure in many countries and are being used as a tool to show the relationship between strains and clones. Although many MRSA genotypes and clonal clusters have been identified in different geographic regions, certain gene clones are predominant in some regions (26)(27)(28)(29)(30). For example, in the current study and among 26 MRSA isolates, we found 14 different genotypes.…”
Section: Discussioncontrasting
confidence: 44%
“…This technique is rapid, inexpensive, simple and cost effective for genotyping and mutation screening in DNA sequence [7]. HRM with real-time polymerase chain reaction (PCR) can be used for spa typing hypervariable X region of the spa gene [7][8][9][10][11]. In this technique, DNA strands are distinguished based on the length and percentage of the GC content [11].…”
Section: Introductionmentioning
confidence: 99%